You Set Me Up: Gendered Perceptions of Twitter Communication Among Black Chicago Youth. (April 2020) - Patton, Desmond Upton; Stevens, Robin; Smith Lee, Jocelyn R.; Eya, Grace-Cecile; Frey, William
We sought to identify the key dynamics in the relationship between social media and violence by identifying new mechanisms that elucidate how Internet banging becomes offline violence through the perceptions of the Black and Latino boys and men. We conducted 33 interviews with Black and Latino boys and men aged 14–24 who live in Chicago, have experience with gang violence, and are social media users. In our investigation of the use of social media by boys and young men to navigate neighborhood violence, we uncovered a recurring narrative about gender relationships in violence. Male participants often attributed escalations of violence to girls and young women, beginning with online communications that migrated to face-to-face meetings. They described girls and young women as the precipitators of violence through "set-up" meetings that began under the guise of romance, dating, and courtship. This study provides an in-depth examination of how males perceive girls and young women as unique threats to their personal safety, a narrative we must engage with in order to further current violence prevention efforts. Future research is needed to examine the lived experiences of young women, their experience with and exposure to social media-related gang violence, and their view of social media behaviors of men that may lead to violence.